Integrasi Pasar Spasial Bawang Putih di Provinsi Jawa Tengah Menggunakan Pendekatan Autoregressive Distributed Lag (ARDL) (Jurnal Sosial Ekonomi Pertanian, 2026)
AbstractThe high dependence of Indonesian garlic prices on imports has led to price fluctuations and regional disparities, particularly in several major production centers in Central Java Province. Meanwhile, the decline in garlic production in the Temanggung, Wonosobo, and Karanganyar Regencies has further exacerbated the imbalance between supply and demand, contributing to price fluctuations. Previous studies on Indonesian garlic have largely focused on national or regional price volatility, leaving spatial market integration among production centers within a single province, such as Central Java, empirically underexplored. This study aims to analyze the spatial market integration of garlic among major production regions by simultaneously considering short-term and long-term relationships. This study uses daily price data from 2025 obtained from the Ministry of Trade’s SP2KP and analyzed using the Autoregressive Distributed Lag (ARDL) method, which includes tests for stationarity, causality, and cointegration, as well as estimates of short- and long-term relationships. The results indicate that in the short term, price transmission remains partial and uneven. This indicates that although there is an adjustment mechanism toward equilibrium, market integration efficiency is still influenced by factors such as distribution, market access, and inter-regional connectivity. Meanwhile, in the long run, it is found that the garlic market in Central Java is spatially integrated. This is indicated by the presence of cointegration and a negative and significant Error Correction Term (ECT) value.Keywords: ARDL; Garlic; Price Transmission; Spatial Integration.
Keywords: ARDL; Garlic; Price Transmission; Spatial Integration